Distribution of butterflies along a trekking corridor in the Khangchendzonga Biosphere Reserve, Sikkim, Eastern Himalayas - Chettri, Nakul (Conservation Science, 2015)
Aim The aim of the research was to understand the distribution pattern of butterflies along attitudinal and disturbance gradients in a trekking corridor in Sikkim, India. Location Khangchendzonga Biosphere Reserve, West Sikkim, India. Material and Methods The study focused on two sets of data, one on inventory of species along the trekking corridor and the other on butterfly species and their numbers along the 19 permanent plots measuring 30x40m. Among the 19 plots, four each was laid in degraded forests (canopy cover <40%) and undisturbed forests (canopy cover >40%) within the warm temperate broadleaf forest (1780–2350 m), and five and six in degraded and undisturbed forest respectively in cool temperate sub-alpine forest (2350– 3600 m). The surveys were conducted thrice a season for two seasons. All individuals recorded from the 114 pseudo replicate plots (19 plots, 3 times a season for 2 seasons) and the casual observations were considered for preliminary analysis for dominant families. Key findings Among the 189 species recorded, Nymphalidae family was dominant (44%) followed by Lycanidae (19%) and the least number of species was recorded from Riodinidae (1%). Likewise, 69% of the species recorded were found to be ‘fairly common’, 16% ‘common’ and 11% rare. The highest number of species per transect was recorded from the disturbed condition (7.1±0.7 Standard Error) at warm temperate broadleaf forest (WTBF) followed by undisturbed condition (6.7±0.8) and the least was recorded at the undisturbed condition (4.1±0.5) of cool temperate subalpine forest (CTSF). Similarly, the butterfly species diversity, its richness and evenness significantly differed between the forest types i.e. WTBF and CTSF and showed negative correlation along altitudinal gradients. Conservation implications Study concludes that the human interventions and tourism enterprises are bringing subtle changes in butterfly habitat and may have major effects on some of the habitat specific species if they are not seriously considered in the management interventions. Conservation Science Vol.3(1) 2015: 1-10